2002
DOI: 10.1136/jcp.55.6.446
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Replens(R) on vaginal cytology in the treatment of postmenopausal atrophy: cytomorphology versus computerised cytometry

Abstract: Replens did have an effect on vaginal morphology. The automated procedure may be useful for the assessment of maturation in vaginal smears and is more sensitive to small (subvisual) changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 6 publications
1
48
0
3
Order By: Relevance
“…Given the equivalent effect on symptoms, use of the lower dose may be prudent. Alternatively, the effect of the higher dose on the thinness of the vaginal epithelium may be associated with greater effectiveness, similar to the difference between symptom improvement with topical estrogens, which reverse the cytologic changes of vaginal atrophy, and with Replens, which does not [8].…”
Section: Discussionmentioning
confidence: 99%
“…Given the equivalent effect on symptoms, use of the lower dose may be prudent. Alternatively, the effect of the higher dose on the thinness of the vaginal epithelium may be associated with greater effectiveness, similar to the difference between symptom improvement with topical estrogens, which reverse the cytologic changes of vaginal atrophy, and with Replens, which does not [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, a Cochrane Review found intravaginal estrogen preparations to be the most effective means to alleviate the symptoms of vulvovaginal atrophy [45]. While some women have symptoms of vaginal dryness ameliorated with regular use of Replens, it has not been shown to improve the maturation index of the vaginal lining [46], or reduce vaginal pH [47]. The effect that Replens has on the incidence of urinary tract infections has not been formally studied.…”
Section: Management Of Urogenital Symptoms In the Non-breast Cancer Pmentioning
confidence: 99%
“…E-mail: Abbaspoorzahra7@Yahoo.com. from a combination of atrophic changes in the estrogen dependent cells that line the vagina and a reduction in the secretion of cervical mucus which circulates in the vaginal lumen (vander Laak et al, 2002).…”
Section: Introductionmentioning
confidence: 99%